Citrus Whitefly Parasitoid, Encarsia lahorensis (Howard) (Insecta: Hymenoptera: Aphelinidae) - Ru Nguyen (EDIS, 2002)
This document is EENY-244 (originally published as DPI Entomology Circular No. 290), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2001.